Whole-exome sequencing reveals Kawasaki disease susceptibility genes and their association with coronary artery lesion - Wang, Yazhou; Chen, Xuepeng; Zhang, Dufei; Chen, Renwei; Alifu, Ailixiati (Frontiers in Pediatrics, 2024)
This study aimed to explore Kawasaki disease (KD) susceptibility genes and their complications like coronary artery lesions (CAL) using whole exome sequencing (WES). Methods: Between April 1, 2021, and December 31, 2022, our study included 55 pediatric patients diagnosed KD at our center, alongside a cohort of healthy children who sought medical care at our institution during the same timeframe. We extracted peripheral blood DNA from all participants and employed the advanced high-throughput Illumina Next-Generation Sequencing technology for comprehensive analysis. Through bioinformatics evaluation, we identified potential susceptibility genes. Moreover, from the 55 KD patients, we selected 15 for the CAL group and 40 for the non-CAL group. We aimed to investigate whether there were significant differences in the allele frequencies of the targeted susceptibility genes between these subgroups, to explore the risk alleles associated with the development of CAL in KD. Results: HLA-DRB1 rs17882084 and IL6ST rs781455079 genotypes and alleles differed significantly between KD and non-KD (P<0.05). No differences existed for IL17RC rs143781415 and VEGFB rs776229557 (P>0.05). No differences in HLA-DRB1 rs17882084, IL6ST rs781455079, and VEGFB rs776229557 genotypes existed between CAL and non-CAL groups (P>0.05). However, the IL17RC rs143781415 genotype differed significantly between them (P<0.05). Conclusions: HLA-DRB1 rs17882084 and IL6ST rs781455079 genotypes may be potential KD susceptibility gene candidates. Specifically, HLA-DRB1 rs17882084 GA genotype and A allele, and IL6ST rs781455079 TC genotype and C allele may increase KD risk. Additionally, the IL17RC rs143781415 genotype may increase CAL risk in KD patients.